2019
DOI: 10.12659/msm.911888
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dome-Shaped Titanium Mesh Cages on Cervical Endplate Under Cyclic Loading: An In Vitro Biomechanics Study

Abstract: BackgroundThis study aimed to verify the anti-subsidence ability of dome-shaped titanium mesh cage (TMC) used in anterior cervical corpectomy and fusion (ACCF).Material/MethodsThirty fresh human cervical vertebrae specimens were collected and randomly harvested into 2 groups: the traditional TMC group and the dome-shaped TMC group. The bone mineral density (BMD) of the specimens was recorded. Each group was biomechanically tested in axial compression with a cyclically loading range from 60 to 300 N at 0.5Hz fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The mismatch between the prostheses and endplate can cause subsidence which induces fixation looseness and reoperation [ 50 , 51 ]. Previous research found that dome-shaped TMC can significantly reduce the subsidence, and matching with the endplate can also increase the maximum load by 53.8% [ 52 , 53 ]. In this study, we established that the lower endplate of the C4 had an arched shape, and thus a dome-shaped supporting structure of the upper artificial disc was designed (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mismatch between the prostheses and endplate can cause subsidence which induces fixation looseness and reoperation [ 50 , 51 ]. Previous research found that dome-shaped TMC can significantly reduce the subsidence, and matching with the endplate can also increase the maximum load by 53.8% [ 52 , 53 ]. In this study, we established that the lower endplate of the C4 had an arched shape, and thus a dome-shaped supporting structure of the upper artificial disc was designed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Based on nIBA (Table 2 ), the oblique angle of the intermediate artificial vertebra was designed to be 10°. Previously, Lu and Wang proposed that an oblique angle could improve mechanical capacity [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The bending strength, tensile strength, compressive strength, and elastic modulus of the n-HA/PA66 strut are similar to those of human bone, but the osteoconductivity and osseointegration characteristics of the prosthetics are still insufficient for clinical applications. Wang et al [ 8 ] conducted in vitro biomechanical studies on a dome-shaped TMC, finding it has stronger resistance to subsidence than normal TMC, but the clinical effect of the dome-shaped TMC needs to be further verified. Lu et al [ 9 ] used a new type of 3D-printed anatomy adaptive titanium mesh cage (3D-printed AA-TMC) to treat CSM and ossification of the posterior longitudinal ligament (OPLL).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, after partial vertebrectomy, titanium mesh is commonly used to support and fuse the vertebral body [13][14][15][16][17][18][19]. Research by the Lu team suggests that titanium mesh cages (TMC) can provide su cient biomechanical stability and have high clinical e cacy.…”
Section: Introductionmentioning
confidence: 99%